A Diene‐Containing Noncanonical Amino Acid Enables Dual Functionality in Proteins: Rapid Diels–Alder Reaction with Maleimide or Proximity‐Based Dimerization. (14th May 2019) - St. Amant, Andre H.; Huang, Fengying; Lin, Jia; Rickert, Keith; Oganesyan, Vaheh; Lemen, Daniel; Mao, Shenlan; Harper, Jay; Marelli, Marcello; Wu, Herren; Gao, Changshou; Read de Alaniz, Javier; et al.
Abstract: Here, we describe a diene‐containing noncanonical amino acid (ncAA) capable of undergoing fast and selective normal electron‐demand Diels–Alder (DA) reactions following its incorporation into antibodies. A cyclopentadiene derivative of lysine (CpHK) served as the reactive handle for DA transformations and the substrate for genetic incorporation. CpHK incorporated into antibodies with high efficiency and was available for maleimide conjugation or self‐reaction depending on position in the amino acid sequence. CpHK at position K274 reacted with the maleimide drug‐linker AZ1508 at a rate of ≈79 m −1  s −1 to produce functional antibody–drug conjugates (ADCs) in a one‐step process. Incorporation of CpHK at position S239 resulted in dimerization, which covalently linked antibody heavy chains together. The diene ncAA described here is capable of producing therapeutic protein conjugates with clinically validated and widely available maleimide compounds, while also enabling proximity‐based stapling through a DA dimerization reaction. Abstract : Eine Dien‐haltige nichtkanonische Aminosäure (ncAA) geht nach dem Einbau in Antikörper Diels‐Alder(DA)‐Reaktionen mit normalem Elektronenbedarf ein. Ein Cyclopentadien‐Derivat von Lysin (CpHK) diente als reaktive Spezies für DA‐Transformationen und als Substrat für die genetische Inkorporierung. CpHK wurde mit hoher Effizienz in Antikörper eingebaut und stand je nach Position in der Aminosäuresequenz für die Maleimid‐Konjugation oder Selbstreaktion zur Verfügung.